2
$\begingroup$

I need to show that $$\int_{-\pi}^{\pi}\left|\frac{a_0}{2}+\sum_{n=1}^{\infty}\alpha_n\cos(nx-\theta_n)\right|^2dx=2\pi\left(\frac{a_0^2}{4}+\frac12\sum_{n=1}^{\infty}\alpha_n^2\right)\tag{1}$$

Just for reference the trigonometric Fourier series is $$f(x)= \frac{a_0}{2} + \sum_{n=1}^{\infty}\left(a_n\cos(nx)+b_n\sin(nx)\right)$$ and the connection between the trigonometric Fourier series and the power spectrum is given by $$a_n=\alpha_n\cos\theta_n$$ $$b_n=\alpha_n\sin\theta_n$$ $$\alpha_n^2=a_n^2+b_n^2$$ $$\tan\theta_n=\frac{b_n}{a_n}$$


So I start by expanding the LHS of $(\mathrm{1})$

$$\int_{-\pi}^{\pi}\left\{\frac{a_0^2}{4}+a_0\sum_{n=1}^{\infty}\alpha_n\cos(nx-\theta_n)+\left[\sum_{n=1}^{\infty}\alpha_n\cos(nx-\theta_n)\right]^2\right\}dx$$ $$= \int_{-\pi}^{\pi}\frac{a_0^2}{4}dx+a_0\int_{-\pi}^{\pi}\sum_{n=1}^{\infty}\alpha_n\cos(nx-\theta_n)dx+\int_{-\pi}^{\pi}\left[\sum_{n=1}^{\infty}\alpha_n\cos(nx-\theta_n)\right]^2dx$$ $$= 2\pi\frac{a_0^2}{4}+a_0\int_{-\pi}^{\pi}\sum_{n=1}^{\infty}\alpha_n\cos(nx-\theta_n)dx$$ $$+\int_{-\pi}^{\pi}\sum_{n=1}^{\infty}\alpha_n\cos(nx-\theta_n)\sum_{m=1}^{\infty}\alpha_m\cos(mx-\theta_m)dx\tag{2}$$

I don't know how to proceed any further with this but do I know that for integer $n\ne m$ $$\langle\cos(nx)|\cos(mx)\rangle=0$$ but I am struggling to apply the same logic to $(\mathrm{2})$ as the cosines have different phase offsets, I am also confused about how to deal with the 2 sums in the second integral.


The answer just states that:

Parseval


Does anyone have any advice on how I can complete this proof?

$\endgroup$
  • 1
    $\begingroup$ You have to argue why the infinite sum can be exchanged with the integral, and then, as $\cos$ is periodic, we get the same integrals for each $n$ if we drop $\theta_n$.. $\endgroup$ – Berci Nov 26 '18 at 17:40
  • $\begingroup$ @Berci Thanks for your reply, I'm not sure why the infinite sum can be exchanged with the integral. In fact, I don't even understand what you mean by 'exchange'. Could you please elaborate on this in an answer? $\endgroup$ – BLAZE Nov 26 '18 at 19:37
2
$\begingroup$

$$\cos(nx-\theta_n)=\cos(nx)\cos(\theta_n)+\sin(nx)\sin(\theta_n)$$

Therefore $$\int_{-\pi}^\pi \cos(nx-\theta_n)\cos(mx-\theta_m)dx={\cos(\theta_n)\cos(\theta_m)\int_{-\pi}^\pi \left(\cos(nx)\cos(mx)\right)dx \quad\text{etc.}}$$

For $n\ne m$, $$\int_{-\pi}^\pi \cos(nx)\cos(mx)dx=0$$ and in general $$\int_{-\pi}^\pi \cos(nx)\sin(mx)dx=0$$ Meanwhile $$\int_{-\pi}^\pi \cos^2(nx)dx=\pi$$ This will allow you to complete $(2)$.

$\endgroup$
  • $\begingroup$ I don't know who edited my answer. Moreover I don't see the point of it. $\endgroup$ – herb steinberg Nov 26 '18 at 20:48
  • $\begingroup$ It was me that edited the format of your answer. Do you not agree that it is easier to read now? If not you can revert back to the original. $\endgroup$ – BLAZE Nov 27 '18 at 15:01
  • $\begingroup$ It is just more spread out. I have found from past experience that reverting to the original is too troublesome, so leave it. $\endgroup$ – herb steinberg Nov 27 '18 at 16:54

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.